+0  
 
0
285
2
avatar

4p- 6p = 0

Guest Mar 27, 2017
 #1
avatar
0

p=0 or p=1.5

Guest Mar 27, 2017
 #2
avatar+7096 
+2

Guest got the right answers but here's an explanation:

4p2 - 6p = 0

 

Factor out a p from both terms.

(p)(4p - 6) = 0

 

Set each factor equal to zero.

(If either one was zero, then the whole thing equals zero.)

Either        p = 0          or       4p - 6 = 0

                                                     p = 6/4 = 1.5

hectictar  Mar 27, 2017

13 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.